Affectation of the Participatory Budgeting exercise in 2012 in the Engativa locality budget, Bogotá D.C., in validity 2013 (2014)
The phenomenon that turned out to be the application of the Participatory Budgeting (PB) in Porto Alegre (Brazil) in 1989, expanded worldwide. Replicating successfully in Brazil itself and other countries, including Colombia, the PB is been established, without being a panacea, in a model to be followed since it achieves the active citizen participation in the public government policies, specifically in the public budget of the community. In Bogotá DC (Colombia) drew attention in the exercise that has been developed about ten years in the implementation of participatory budgeting, how it developed and if that exercise has had a significant impact on the implementation of the district budget in fiscal year 2013, to that aim it will be taking into account the exercise done in the locality of Engativa (Bogotá D.C) in 2012 and its incidence in the 2013 district budget, if so, it will generate a significant change in representative democracy to which we are accustomed to pass in part to a true democracy of grassroots participation in society.